Food Security Model at Household Level on Horticulture Village - Dadang Sukandar (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2004)
The Objective of this study is to formulate operational concept of Food Security at household level and to formulate the indicator of food security on Horticulture Village. Renggasbandung is a research location where 60 household were selected through stratified random sampling with proportional alocation. Data collected were food consumption, expenditure, education, house condition and agricultural data. Food security indicator were determined by applying correlation analysis and discriminant analysis to obtaine food security model. House size (m2/capita), number of chicken and electricity capacity are obtained as component of food security model at household for Horticulture Village. Keywods : Food security.